Analysis of the Feasibility of Universal Basic Income in Colombia: A Grounded Theory Study (2024)
This paper shows the results of research conducted with the objective of knowing the perceptions of people in Colombia about the possibility of receiving a universal basic income, which does not exist thus far in the country. The research question was: how do the social perceptions of Colombians about receiving a UBI allow them to understand the possibilities of developing a public policy that guarantees it? A qualitative methodology of grounded theory was applied by conducting 37 in-depth interviews with adults of all socioeconomic levels, all educational levels and productive working age. The information obtained was coded. The resultant main categories with which the Grounded Theory was built were mistrust in others, hope for a better society, unconditional support, and implementation scenario. It was concluded that, if there is an intention to implement the UBI in Colombia, there must be policies that contribute to changing the mistrust and fear of citizens to receive support from the State by solidarity and equity so that UBI can be assume as a right that contributes to the construction of justice and social welfare.